Separation of Lactic Acid Produced by Hydrothermal Conversion of Glycerol Using Ion-Exchange Chromatography. Issue 2 (February 2015) - Arcanjo, M.R.A.; Fernandes, F.A.N.; Silva, I. J.
Production of lactic acid by hydrothermal conversion of glycerol is an option to add value to the large amounts of glycerol that is being generated during the production of biodiesel. This work aimed to separate lactic acid by ion-exchange resins in a fixed-bed column. Adsorption isotherms were obtained from the breakthrough curves using different initial concentrations of lactic acid (60–302 g/l) and temperatures (30, 40 and 60 °C). Maximum adsorption capacities were estimated by the Langmuir model. Adsorption and desorption cycles for a binary and a real mixture were performed. The methodology proposed for the separation of lactic acid in a fixed-bed column presented high values of adsorptive capacity for both Amberlite IRA-96 and Amberlite IRA-67 resins at 30 °C. Lactic acid was more strongly adsorbed by Amberlite IRA-96 than the IRA-67 resin with maximum adsorption capacity of 544 and 341 g/l, respectively. Chromatographic experiments for the single-component solution (lactic acid), binary mixture (lactic acid and glycerol) and real mixture showed high values of recovery (29.2%, 31.3% and 23.5%, respectively) and productivity (3.14, 7.00 and 2.43 kg of lactic acid/kg resin. day).